2013
DOI: 10.1111/1365-2664.12077
|View full text |Cite
|
Sign up to set email alerts
|

Fast‐growing pioneer tree stands as a rapid and effective strategy for bracken elimination in the Neotropics

Abstract: Summary1. Large areas of agricultural land around the world are degraded as a consequence of dominance by bracken fern (Pteridium spp.). Tropical production systems based on shifting cultivation and cattle breeding are particularly vulnerable to invasion of this species. In spite of this, effective methods for tropical bracken control are limited. 2. Fast-growing tree species have been used successfully to out-compete aggressively colonizing heliophytes and trigger natural succession. Drawing on a traditional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 51 publications
1
31
0
1
Order By: Relevance
“…In the long term, bracken control should reduce the amount of bracken available and hence the risk that ptaquiloside may pose to drinking water. However, recent studies have demonstrated that it takes over 10 years to fully control bracken [45], and, with the recent ban on asulam, land managers are reverting to mechanical control techniques. Cutting and rolling are typically carried out one to three times a year for several years.…”
Section: Discussionmentioning
confidence: 99%
“…In the long term, bracken control should reduce the amount of bracken available and hence the risk that ptaquiloside may pose to drinking water. However, recent studies have demonstrated that it takes over 10 years to fully control bracken [45], and, with the recent ban on asulam, land managers are reverting to mechanical control techniques. Cutting and rolling are typically carried out one to three times a year for several years.…”
Section: Discussionmentioning
confidence: 99%
“…All species have a limited tolerance for Ecology and Society 21(1): 10 http://www.ecologyandsociety.org/vol21/iss1/art10/ disturbance, and excessive disturbance is a threat to global biodiversity (Turner 2010). Increasing levels of disturbance can accelerate vegetation change (Loehle 1998(Loehle , 2014, may create feedbacks that increase the likelihood of switching from one relatively stable ecological state to another (Beckage et al 2009, Tredennick andHanan 2015), and may permit the establishment of undesirable persistent vegetation (Roos et al 2011, Douterlungne et al 2013 or nonnative species (Moles et al 2012, Jauni et al 2015. Our challenge is to identify and implement some form of more optimal disturbance regime; I am not suggesting we need more disturbance.…”
Section: Implications For Conservationmentioning
confidence: 99%
“…As espécies pioneiras, caracterizadas pelo rápido crescimento e alto potencial de cobertura do solo, favorecem a sucessão florestal, facilitando o estabelecimento das espécies não pioneiras intolerantes à alta irradiância normalmente observada em áreas abertas (Douterlungne et al, 2013). O melhor entendimento do desempenho inicial em campo de espécies florestais nativas por meio da combinação de diferentes grupos ecológicos e as relações interespecíficas existentes constitui um desafio em programas de reflorestamento na região amazônica que naturalmente é caracterizada pela alta diversidade florística (Santos et al, 2006).…”
Section: Methodsunclassified